Forms of Women's Resistance in the Novel “Perempuan yang Menangis kepada Bulan Hitam” and the Novel “Perempuan yang Menunggu di Lorong Menuju Laut” by Dian Purnomo - Liya Yuliyani; Agus Nuryatin; U’um Qomariyah (Universitas Negeri Semarang, 2025)
In recent years, women in Indonesia have experienced various forms of discrimination and harassment. This not only happens in real life but also happens in literary works. So, it is necessary to look further or examine the efforts made by women or women's resistance to overcome these problems. This research aims to reveal forms of women's resistance in the novel